Floristic diversity of the upper river basin Tambo-Ichuña (Moquegua, Peru) - Montesinos-Tubée, Daniel B. (2011)
A study of the floristic diversity of vascular plants is presented from the basin of the Tambo-Ichuña River, the high Andean Puna plateau and wetlands of Ichuña, Ubinas and Yunga Districts (3400 - 4700 m altitude), General Sanchez Cerro Province, Department of Moquegua, Peru. Vascular flora is composed of 70 families, 238 genera and 404 species. The Magnoliopsida represent 78% of the species, Liliopsida 16%, Gymnosperms 0.5% and Pteridophytes 6%. Among lifeforms, the Hemicryptophytes are the most numerous. Three vegetation formations have been identified, the humid scrubland being the most diverse in species richness. Between endemic species, 42 taxa are exclusive to Peru. A total number of 272 new additions of vascular species to the flora of the department of Moquegua are presented.